Development of Learning Media Using Flypaper in Computer and Network Engineering at SMK Negeri 1 Painan - Fancer Rumahorbo; Hasan Maksum; Hansi Effendi; Dori Yuvenda (Universitas Muhammadiyah Enrekang, 2022)
This research aims to produce a learning media using flypaper that is valid, practical, and effective in the basics of computer network engineering and telecommunications. Learning media using flypaper is designed to increase student learning outcomes. The method in this study uses Research and Development (R and D) with the 4-D development model. The data analysis technique uses descriptive techniques to describe the validity, practicality, and effectiveness of learning media using flypaper. The results found from this development research: (1) the validity of learning media using flypaper was declared valid in media validation of 0.86>0.6 and material validation of 0.87> 0.6. (2) The practicality of learning media using flypaper from teacher responses with a value of 91.65% and student responses of 84.94% is declared very practical. (3) The effectiveness of learning media using flypaper is declared effective in improving student learning outcomes. Its concluded that learning media using flypaper is valid, practical, and effective to be utilized as a learning tool in basic network and telecommunication engineering subjects.